2021
DOI: 10.1503/cmaj.202604-f
|View full text |Cite
|
Sign up to set email alerts
|

Incidence de la COVID-19 sur les issues de grossesse: examen systématique et méta-analyse

Abstract: a maladie à coronavirus 2019 , causée par le coronavirus du syndrome respiratoire aigu sévère 2 (SRAS-CoV-2), a fait l'objet d'une déclaration de pandémie en mars 2020 1 . Les personnes enceintes et les nourrissons pourraient être particulièrement susceptibles de contracter la COVID-19, car la grossesse induit des changements physiologiques touchant l'appareil cardiorespiratoire et le système immunitaire, ce qui pourrait altérer la réponse à l'infection par le SRAS-CoV-2 2 . Par ailleurs, le foetus peut être e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Pre-eclampsia and eclampsia cause 7–15% of maternal deaths [ 31 ]. A systematic review with metanalysis suggests that COVID-19 can be associated with an elevated risk of pre-eclampsia, premature birth, and other adverse outcomes during pregnancy [ 32 ]. Studies from the United States, the United Kingdom, India, and Mexico have shown an increase in maternal mortality because of the COVID-19 pandemic [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pre-eclampsia and eclampsia cause 7–15% of maternal deaths [ 31 ]. A systematic review with metanalysis suggests that COVID-19 can be associated with an elevated risk of pre-eclampsia, premature birth, and other adverse outcomes during pregnancy [ 32 ]. Studies from the United States, the United Kingdom, India, and Mexico have shown an increase in maternal mortality because of the COVID-19 pandemic [ 33 ].…”
Section: Discussionmentioning
confidence: 99%